(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
Today, the economy in general and the external environment of the organization in particular are changing quite quickly. In order not to lose the essence of the organization and the purpose for which it was created during such "minute" changes, it is necessary to have a long-term plan of activity, another name for this plan is strategy. Based on the above, the purpose of this article is to describe the concept of strategy and its classification, as well as to promote the application of the strategy in more organizations.